Legitimasi Ketertindasan melalui Narasi Agama di Media Sosial - Arwansyah, OK Dedy; Salam, Abdillah; Yusuf, Rum Ahmad (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study examines the phenomenon of the legitimacy of oppression through religious narratives on social media, especially Instagram. Social media has become an influential space in disseminating religious content that is multi-interpretive, creating passive acceptance of existing socio-economic conditions. Using a qualitative approach and critical discourse analysis, this study analyzes how religious narratives spread through texts and visual elements function as hegemonic tools. The results of the study show that narratives such as "it is better to be poor in this world but rich in the hereafter" reinforce unequal social structures by encouraging the values of surrender and acceptance. This has an impact on various aspects of people's lives, including the economy, education, and social participation, which can slow down progressive social change. This study emphasizes the importance of critical awareness of religious narratives so that people are not trapped in the legitimacy of oppression.